Association of hypertension and dyslipidaemia with increasing obesity in patients with Type 2 Diabetes Mellitus - Zikria Saleem; Hamid Saeed; Zohaib Abbas Khan; Muhammad Imran Hassan Khan; Furqan Khurshid Hashmi; Muhammad Islam; Afzaal Bashir; Saleha Sadeeqa
The study was performed to estimate the association of hypertension and dyslipidaemia with increasing body weight and obesity in Type II diabetics of Lahore, Pakistan. An observational study was conducted by enrolling 2708 obese diabetics from four diabetes care centres of Lahore, Pakistan. Data was collected for a period of 7 months. Associations were estimated using chi-square, binary and multinomial logistic regression. Data suggested that blood pressure, systolic and diastolic, exhibited continual increase with increasing body weight and obesity class in diabetes patients with 41.8% increase in the prevalence of hypertension in obesity class III subjects (OR; 1.91, p=0.02). Likewise, triglycerides and total cholesterol exhibited continual increase in their mean values with increasing obesity, i-e., an overall increase in the prevalence of dyslipidaemia of 27.2% in obesity class 3 subjects (OR; 1.94, p=0.29). Taken together, this data suggested that hypertension is potentially associated with increasing obesity in diabetics, while dyslipidaemia demonstrated plausible association only with obesity class 3.